Influence of Kinesitherapy on Balance Reactions in Patients with Ischemic Stroke in the Chronic Period - Vasileva, Danche (Open Access Maced J Med Sci, 2015)
AIM: The study aims to trace the influence of specialized kinesitherapeutic methodology (SKTM) on balance reactions in patients with ischemic stroke in the chronic period (ISChP). MATERIAL AND METHODS: A prospective, multicenter study with 56 patients with ISChP. Evaluation of balance reactions using Berg Balance Scale - BBS, includes implementation of 14 tasks with increasing difficulty reflecting the usual activities of everyday life. The first 5 assignments are used to assess the main balance potential and the remaining 9 (6th to 14th task) include more sophisticated balance tasks. RESULTS: The patients were found with a significant improvement in balance opportunities, according to the scale of Berg. Compared to initial data there is a significant increase in the number of points in the measured indicators for functional and static balance. In absolute terms, positive change is most pronounced during the 1st month with a level of significance of p <0.001. CONCLUSION: The applied specialized kinesitherapeutic methodology continued later as adapted exercise program at home, and significantly improved equilibrium reactions in patients with postural disorders because of ischemic stroke and is with a supportive prolonged exposure.